URGENSI ENTERPRISE INFORMATION MANAGEMENT PADA PENINGKATAN KEAMANAN DATA PERUSAHAAN - Nur Illah, Aina; Putri Roro Andini; Yusuf Amrozi (Universitas Islam Indonesia, 2024)
The application of information technology has become a key requirement in the industrial sector. However, rapid digitalization also brings risks in the form of increasingly complex data security threats. Enterprise Information Management (EIM) emerges as a comprehensive solution that integrates technology, business processes, and data management to improve the security and efficiency of company operations. This research uses a literature study approach by analyzing six relevant journals regarding the implementation of EIM in Indonesian companies in the last five years. The results show that EIM can improve data security through encryption, role-based access control, and real-time activity monitoring. This study identifies various effective methods implemented by companies, such as ISO/IEC 27001 standards, Advanced Encryption Standard (AES) algorithms, and Artificial Intelligence (AI)-based solutions. By adopting EIM, companies can not only reduce the risk of data leakage but also ensure compliance with international regulations and strengthen competitiveness in the era of digital transformation.